Pengaruh Store Atmosphere, Lokasi dan Gaya Hidup Terhadap Keputusan Pembelian di Foresthree Coffee Kabupaten Dharmasraya - Rina Rina; Yesi Gusteti; Kelik Purwanto (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This study was conducted to determine the effect of store atmosphere, location and lifestyle on purchase decisions at Foresthree Coffee Dharmasraya Regency. The purpose of this study is to analyze and explain the effect of store atmosphere, location and lifestyle partially and simultaneously on purchasing decisions at Foresthree Coffee Dharmasraya Regency. This study used quantitative research methods with data collection using questionnaires conducted in February to March 2023. The sample in this study was 392 respondents obtained from the number of visitors to Foresthree Coffee Dharmasraya Regency for five months from September 2022 to January 2023, which was 20,698 respondents. The data analysis techniques used in this study are validity test, reliability test, correlation analysis, multiple linear regression analysis, classical assumption test, t test, f test and determination test (R2). The results of this study indicate that variables of store atmosphere, location and lifestyle partially and simultaneously have a positive and significant effect on purchase decisions. The adjusted R2 value is 0.653 which means that all independent variables affect the dependent variable by 65.3%. While the remaining 34.7% is influenced by other factors not tested in this study.